Path tracking control of a snake robot with a passive joint. (3rd April 2023) - Sakakibara, Kazunori; Ariizumi, Ryo; Asai, Toru; Azuma, Shun-ichi
Abstract : The highly redundant nature of a snake robot will enable the robot to complete its task even with a passive joint caused by an actuator failure. However, existing control methods cannot be applied to a snake robot with a passive joint. This paper proposes a control law that achieves linear path-following control of a snake robot with a passive joint. The effectiveness of our control method is shown via numerical simulation and experiment. GRAPHICAL ABSTRACT: UF0001